SOCIAL DETERMINANTS IN A LOW-INCOME POPULATION WITH HEART FAILURE - Nidhish Lokesh, BS; Aditya Nagori, PhD; Neil Keshvani, MD; Ambarish Pandey, MD; Andrew Sumarsono, MD MPH (Elsevier, 2023)
Therapeutic Area: Heart Failure Background: The association of social determinants of health (SDOH) and heart failure (HF) outcomes is well-established. However, most HF SDOH measures are obtained in the ambulatory setting, and the distribution of SDOH among hospitalized patients for HF is poorly understood. Methods: We conducted a prospective, cross-sectional study to identify the prevalence of SDOH among patients hospitalized with HF at Parkland Memorial Hospital (PMH), Dallas's safety-net hospital. English- or Spanish-speaking patients hospitalized for HF were eligible to participate. We excluded patients in police custody or jail. Using a panel of validated surveys, we collected data across the following 10 SDOH domains: housing instability, financial health, food security, cost-related nonadherence, transportation barriers, social support, interpersonal violence, discrimination, health literacy, and health numeracy. We extracted clinical data including substance use and left ventricular ejection fraction (LVEF). We used summary statistics to calculate the overall prevalence of SDOH burden. We compared SDOH between race/ethnic subgroups using chi-square tests and t-tests. Results: 118 individuals were included (Mean age 53, 75.4% male, 15.3% Non-Hispanic White (NHW), 61.9% Non-Hispanic Black (NHB), 20.3% Hispanic, 2.5% Other). The average LVEF was 30%. The mean number of positive SDOH domains was 5.0. Seven in eight participants reported at least 3 positive SDOH domains. The median income was $13,200 and 63.1% of participants were below 130% of the federal poverty limit. The most prevalent SDOH included discrimination (87.3%), poor financial health (78.0%), and transportation barriers (67.8%). Over half of patients reported at least some food insecurity. 47.5% had at least one form of substance use disorder. When stratified by race/ethnicity, there were differences in being married (16.7% NHW, 17.8% NHB, 45.8% Hispanic, 0% Other, p=0.02), having access to a vehicle (66.7% NHW, 46.6% NHB, 79.2% Hispanic, 66.7% Other, p=0.03), and having savings (11.1% NHW, 9.6% NHB, 16.7% Hispanic, 66.7% Other, p=0.03). Conclusions: In this single-center, prospective study, we demonstrate substantial overall SDOH burden in low-income patients hospitalized with HF. Future studies will evaluate how HF outcomes are affected by targeting modifiable, highly prevalent SDOH.